Proximal and distal domains that control in vitro transcription of the adenovirus IVa2 gene. - Natarajan, V (1984)
The adenovirus IVa2 gene, which is expressed at an intermediate time in the viral infectious cycle, is separated from the adenovirus major late promoter (MLP) 5' start site by 210 base pairs and is transcribed from the opposite strand. In contrast to the MLP, the IVa2 gene does not contain a "TATA" box upstream from its 5' start sites. By using a series of deletion mutants, two upstream control regions that are rich in cytidine residues, one proximal to the cap site at nucleotide positions -39 to -48 and a distal domain between nucleotide positions -152 and -242 have been identified as essential for IVa2 transcription (IVa2 cap site is nucleotide position + 1). Transcription efficiency is decreased by 70-90% after the deletion of a proximal C-rich domain when either linear or supercoiled DNAs were used as template. However, distal sequences functioned as transcriptional control domains only with covalently closed DNA templates. The deletion of both the proximal and distal regions from covalently closed DNA templates reduces the levels of IVa2 transcription by a factor of 100-150. When the plasmid pAd242 that contains the 5' start sites of adenovirus MLP and IVa2 is transcribed, there is essentially a complete suppression of transcription of the adenovirus IVa2 gene. The transcription efficiency of IVa2 is increased 10-fold after deletion of the MLP cap site. A model based on a shared entry site for RNA polymerase II and competition between major late and IVa2 promoters is proposed to explain the in vitro transcriptional results.